Analyse von Steueramnestiedaten - Michael Haug; Luise Hölscher; Andreas Schweinberger (Frankfurt School of Finance & Management, 2008)
Tax fraud is a serious problem for fiscal authorities worldwide, not only in countries regarded as hightax like Germany. Besides longterm tax reforms, tax amnesties are used to bring back taxable amounts into the legal sector. The German tax amnesty of 2004/2005 was one of the last examples in Europe and was - like other tax amnesties before - of limited success. This paper uses a given database with 126 tax amnesties between 1981 and 2005 in several countries worldwide. Aim is to develope predictions about the fiscal success or failure of a tax amnesty, depending on its structure and legal plus economic background.
urn:nbn:de:101:1-2008100610
Keywords: H26; K42; 340; Steuerhinterziehung; Steueramnestie; lineare Regression; Tax fraud; Tax amnesty; linear regression